Решение
z^4-4z^3-27z^2-38z-16=0
z = - 1
z⁴ - 4z³ - 27z² - 38z - 16 I z + 1
- z³ - 5z² - 22z - 16
z⁴ + z³
----------------------------------
- 5z³ - 27z² - 38z - 16
-
- 5z³ - 5z²
-----------------------------------
- 22z² - 38z - 16
-
- 22z² - 22z
--------------------------
- 16z - 16
-
- 16z - 16
___________
0
z⁴ - 4z³ - 27z² - 38z - 16 = (z + 1)*( z³ - 5z² - 22z - 16)
z³ - 5z² - 22z - 16 = 0
z = - 1
z³ - 5z² - 22z - 16 I z + 1
- z² - 6z - 16
z³ + z²
---------------------------
- 6z² - 22z - 16
-
- 6z² - 6z
------------------------
- 16z - 16
-
- 16z - 16
-------------------
0
z³ - 5z² - 22z - 16 = (z + 1)*(z² - 6z - 16)
z⁴ - 4z³ - 27z² - 38z - 16 = (z + 1)² * (z² - 6z - 16)
z² - 6z - 16 = 0
Применим теорему Виета
z₁ + z₂ = - p
z₁ * z₂ = q
z₁ + z₂ = - (- 2 + 8) = - 6
z₁ * z₂ = - 2 * 8 = - 16
z = - 2
z = 8
Ответ: z₁ = z₂ = - 1; z₃ = - 2; z₄ = 8